HOTS-Based e-evaluation Quizwhizzer in science learning in elementary schools - Farida Nur Kumala; Intan Safitri; Triwahyudianto Triwahyudianto; Arnelia Dwi Yasa; Moh Salimi (Inovasi Kurikulum, 2024)
Teachers have’nt implemented HOTS-based questions for learning evaluation, resulting in students' low thinking abilities. This research aims to develop HOTS-based E-evaluation using the Quizwhizzer application. This research uses the ADDIE model with various stages, namely (1) the analysis stage, curriculum analysis, student character, and learning evaluation are carried out; (2) the design stage, learning materials are determined, HOTS questions and research instruments are prepared; (3) the development stage, validation of the suitability of the material, language and media is carried out; (4) the implementation stage, a validation test of the practicality and effectiveness of the application is carried out; (5) the final, evaluation stage was carried out to find out deficiencies in the application. The research subjects were 28 class IV students at SDN Mulyorejo 3. The instruments used are tests and questionnaire sheets. The research results showed that the E-Evaluation of the feasibility test was 90 percent from material experts, 96 percent from language experts, and 92 percent from media experts. The results of teacher practicality were 95 percent, students were 92 percent and effectiveness showed that there was an increase in students' HOTS abilities." HOTS-based e-evaluation using the quizwhizzer application can increase students' HOTS in science learning.   Abstrak Guru belum menerapkan soal-soal berbasis HOTS untuk evaluasi pembelajaran sehingga berakibat kemampuan berpikir peserta didik yang rendah. Tujuan penelitian ini untuk mengembangkan E-evaluation berbasis HOTS menggunakan aplikasi Quizwhizzer. Penelitian ini menggunakan model ADDIE dengan berbagai tahapan yaitu (1) tahap analyis dilakukan analisis kurikulum, karakter peserta didik, dan evaluasi pembelajaran; (2) tahap design dilakukan penentuan materi pembelajan, menyusun soal HOTS dan instrument penelitian; (3) tahap development dilakukan validasi kelayakan materi, bahasa, dan media; (4) tahap implementation dilakukan uji validasi kepraktisan dan keefektifan aplikasi; (5) terakhir, tahap evaluation dilakukan untuk mengetahui kekurangan pada aplikasi. Subyek penelitian ialah peserta didik kelas IV SDN Mulyorejo 3 sejumlah 28 peserta didik. Instrumen yang digunakan yakni test dan lembar angket. Hasil penelitian menunjukkan E-Evaluation dari uji kelayakan sebesar 90 persen dari ahli materi, 96 persen dari ahli bahasa, dan 92 persen dari ahli media. Hasil kepraktisan guru 95 persen, peserta didik 92 persen dan keefektifan yang menunjukkan terdapat peningkatan kemampuan HOTS peserta didik. E-evaluation berbasis HOTS menggunakan aplikasi Quizwhizzer dapat meningkatkan HOTS peserta didik pada pembelajaran IPA. Kata Kunci: e-evaluation; kemampuan berpikir tingkat tinggi; Quizwhizzer